2020
DOI: 10.1371/journal.pone.0229709
|View full text |Cite
|
Sign up to set email alerts
|

Non-spatial information on the presence of food elevates search intensity in ant workers, leading to faster maze solving in a process parallel to spatial learning

Abstract: Experience can lead to faster exploitation of food patches through spatial learning or other parallel processes. Past studies have indicated that hungry animals either search more intensively for food or learn better how to detect it. However, fewer studies have examined the contribution of non-spatial information on the presence of food nearby to maze solving, as a parallel process to spatial learning. We exposed Cataglyphis niger ant workers to a food reward and then let them search for food in a maze. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 95 publications
1
18
0
Order By: Relevance
“…Other studies on the same ant species demonstrated supporting results. First, pre-exposure to food, even out of the maze context, resulted in faster solving times (in comparison to a nonexposed control; Bega et al 2020). Second, switching mazes at mid-experiment slowed food-discovery time, but never down to the level of a naïve colony at its first run (Saar et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies on the same ant species demonstrated supporting results. First, pre-exposure to food, even out of the maze context, resulted in faster solving times (in comparison to a nonexposed control; Bega et al 2020). Second, switching mazes at mid-experiment slowed food-discovery time, but never down to the level of a naïve colony at its first run (Saar et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In short, more successful foraging can result from both spatial learning and higher search persistence (Bega et al . 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, shortening the legs in other studies led to space misperception and the underestimation of movement distances, at least temporarily ( Wittlinger et al 2007 ). However, previous studies on C. niger in mazes of a similar size and complexity revealed differences in food-discovery time and linked them to the type of food reward and previous exposure to food immediately before searching in the maze ( Bega et al 2020 ; Saar et al 2020 ). Second, it is possible that focusing on other foraging-related response variables could result in a stronger effect of injury, such as injured individuals carrying smaller loads or settling for food of lower quality than healthy ones, as demonstrated in bees ( Higginson and Barnard 2004 ; Johnson and Cartar 2014 ).…”
Section: Discussionmentioning
confidence: 98%
“…We expected the deteriorating conditions to make more workers fall into pits and to reach the food reward more slowly than the control because the workers were first trained that a straight path leads to the food reward, a path that is of no use after adding pits. The studied species had already demonstrated its ability to improve quickly in maze-solving owing to a mixture of spatial learning and elevated searching motivation [ 46 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%